Training errors beyond - Nielsen, R. O. (International Calgary Running Symposium, August 14-17, 2014, 2014)
Introduction: Training errors is widely accepted as the main cause of running-related injuries. Unfortunately, the evidence-based knowledge to support this assumption is non-existent possibly because of a number of methodological shortcomings. These shortcoming need to be solved to get beyond the training-error puzzle. In the upcoming years, we may want to: Analyze training-related data differently: Researchers must acknowledge that most exposures and outcomes are time-varying and they need to take this into account if prospective data are collected. Time-to-event statistics enables the researcher to take into account time-dependent exposures and outcomes using multi-state models and take into account competing risks. Start interdisciplinary collaborations: At the IOC conference in Monaco 2014, Dr. Nigg highlighted the need for research which combines experimental biomechanical knowledge with epidemiological clinical knowledge. Interdisciplinary collaborations between researchers may be an important step to get plausible hypothesis which can be tested biomechanically as well as clinically. Quantify distance, pace and strides: The number of strides is quantifiable by the use of accelerometers, which, in addition to the GPS data on distance and pace, enable calculation of a stress-frequency profile for each runner after each running session. Since most runners are able to use their smartphone while running a possibility for massive data collection exists (n > 10000). Complete large-scale prospective studies/trials: At best, the clinical studies need to be designed as large-scale prospective cohort studies or randomized controlled trials in favor of case-control studies, retrospective studies or cross-sectional studies.